Causality in mean and variance between ISE 100 and S&P 500: Turkcell case - Korkmaz, Turhan; Cevik, Emrah I.; Birkan, Elif; Ozatac, Nesrin (Academic Journals, 2011)
The article examines the causality between US stock market and Turkish stock market by using two-step method which is developed by Hong ( 2001). The returns of Turkcell securities that are traded as American Depository Receipt in the New York Stock Exchange and ISE 100 are used. The causality test results indicate that S&P 500 affects ISE 100 and Turkcell returns, moreover, Turkcell returns influence each other. Consequently, it can be seen that there is a spillover effect from US stock market to Turkish stock market.
Keywords: Turkcell; S&P 500; ISE 100; ADR; causality